1995
DOI: 10.1021/ma00111a027
|View full text |Cite
|
Sign up to set email alerts
|

Multimolecular aggregation of mononucleosomal DNA in concentrated isotropic solutions

Abstract: We study semidilute and concentrated solutions of mononucleosomal DNA at three different NaCl concentrations by static and dynamic light scattering, viscosity, and electron cryomicroscopy. At low enough DNA concentrations the second virial coefficient behaves in the usual manner and can be interpreted by a charged rod model. It is possible to understand the concentration and scattering vector dependence of the scattering with the help of recent theoretical analyses of semidilute solutions of charged rods. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 14 publications
10
89
0
Order By: Relevance
“…Similar to reports of DNA, tobacco mosaic virus (TMV), and xanthan self-interactions, heparin is another example of a highly negative, linear biological macromolecule that displays strong self-interactions [19,20]. Interestingly, we have found that only a small fraction of heparin actively interacts as estimated from previous rheological measurements [3,5].…”
Section: Discussionsupporting
confidence: 85%
“…Similar to reports of DNA, tobacco mosaic virus (TMV), and xanthan self-interactions, heparin is another example of a highly negative, linear biological macromolecule that displays strong self-interactions [19,20]. Interestingly, we have found that only a small fraction of heparin actively interacts as estimated from previous rheological measurements [3,5].…”
Section: Discussionsupporting
confidence: 85%
“…There is limited research in the literature on the dimensional properties of polypeptides indicating a head-to-tail dimerization for PBLG in 1,2-dichloroethane by light scattering. 39,40 Therefore, the chain extension phenomenon by dilution for these 2 polypeptides reported in this work is a novel observation.…”
Section: Dynamic Light Scattering Results Related To Chain Extension supporting
confidence: 50%
“…27 Attractive interactions of nonelectrostatic origin may also play a role in solutions of highly charged polyelectrolytes. 28,33 In the present solutions, the power law dependence is followed by a linear region (0.02 Å À1 < q < 0.1 Å…”
mentioning
confidence: 72%